Acute pain service organization - (:unkn) unknown (My University, 2005)
Objective: The aim of this retrospective study was to evaluate the organization of acute pain service of Marmara University Hospital, and the efficacy, side effects and complications of the analgesic methods used between September 2003-2004. Materials and Methods: Data sheets of the postoperative pain survey of 3190 patients treated by the acute pain service were examined retrospectively between September 2003 and 2004. Analgesic methods used and complications related to them, numeric rating scale (NRS) scores, TORDA scores and patient's satisfaction were recorded. Results: The incidence of additional analgesic requirement (NRS>3) in epidural intermittent group were higher than the other groups (p<0.05). The incidence of nausea and vomiting were higher in intravenous patient controlled analgesia and epidural patient controlled methods compared to other groups. Pruritis was less prominent in parenteral intermittent group compared to other groups. 98% of the patients were satisfied with the analgesic method performed. Conclusion: Acute pain service organization provides maximum satisfaction either in patients treated with invasive methods such as regional blocks or in patients treated with simple and noninvasive methods such as the administration of parenteral / oral nonsteroidal anti inflammatory agents and opioids.
Keywords: Analgesia: postoperative; Anesthetic techniques: epidural; Pain: acute pain service